PARTISIPASI POLITIK PEREMPUAN DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA KARETAN: ANALISIS PERSPEKTIF FEMINISME LIBERAL - aiman zikri; Agus Fauzi; Ahmad Ridwan (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2026)
This study aims to evaluate the form and quality of women's political involvement in the Village Development Planning Deliberation (Musrenbangdes) in Karetan Village using a liberal feminist perspective that emphasizes the equality of rights, opportunities, and freedoms of women in the public decision-making process. The method used in this study is qualitative with data collection techniques through in-depth interviews, direct observation, and document collection to understand gender interactions in the village deliberation forum. The research findings indicate that women in Karetan Village structurally have good access to Musrenbangdes through village officials, women's organization networks, and community communication media. However, the quality of women's participation still varies. Women involved in organizations such as the PKK tend to be more active in expressing opinions and proposing programs, while women who are not members of social organizations often play a passive role due to psychological barriers, limited organizational experience, and domestic burdens. Women's contributions to the deliberations are more focused on issues such as public health, family education, environmental cleanliness, and strengthening the household economy, thereby enriching the village development agenda which was previously more focused on infrastructure. From a liberal feminist perspective, these findings indicate that formal equality is beginning to be realized, but substantive equality still requires capacity building, social support, and women's empowerment strategies so that participation in village development becomes more inclusive.